Physicochemical and rheological properties of rice flour and starch from Malaysian rice cultivars - Mohd Effendi, Mas Amalia; Ahmad Redza, Maryam Shahwis; Mohsin, Aliah Zannierah; Shukri, Radhiah; Meor Hussin, Anis Shobirin; Berahim, Zulkarami; Sukor, Rashidah (Hibiscus Publisher Enterprise, 2024)
Starch consists of amylose and amylopectin polysaccharides that vary in different rice varieties. The development of new rice varieties has presented the need for characterization to determine their applications. This study aims to determine rice flours' physicochemical and rheological properties and starches from two Malaysian varieties, UPM Putra 2 (P2) and NMR 152 (NMR). P2 and NMR flours and starches were analysed for proximate amylose content, pasting, and rheological properties with commercial white rice (JM) as control. P2 and NMR starches had lower amylose contents than JM; meanwhile, their flours contained higher fat, total dietary fiber, and ash than JM flour. Based on thermal analysis, P2, and NMR exhibited similar peak viscosity but differed in breakdown and setback temperatures and final viscosity. Starch gels exhibited solid-like behaviour as their G' was greater than G", and tan δ values were smaller than unity. In conclusion, pasting and rheological properties of rice flours and starches varied for different rice varieties even though both P2 (23.1%) and NMR (23.4%) are medium-amylose starches, while JM (26.6%) is high-amylose starch. The characterization of these rice and starch is essential for them to be further processed into various food products.